Prediction and quality evaluation of quality markers of Gentiana scabra Bunge. in treatment of liver injury - Liu, Jiayi; Yu, Xuelin; Luo, Jiayi; Wang, Dan; Yin, Haibo (Frontiers in Pharmacology, 2025)
IntroductionGentiana scabra Bunge. (GSB) has been demonstrated to exert nourishing effectson the liver and gallbladder. Notably, GSB extract has a marked therapeutic effect on liver injury (LI). However, the quality markers (Q-markers) of GSB associated with this effect remain unclear. Moreover, no study to date has evaluated the quality of GSB from different producing areas based on such Q-markers.MethodsThe aim of this study was to identify the Q-markers of GSB that define its therapeutic efficacy against liver injury. This was achieved through establishing HPLC fingerprints and conducting “small molecule–protein” interaction screening, followed by verification using in vitro cell experiments. Finally, the identified Q-markers were quantified to assess the quality of GSB samples from different producing areas.ResultsFirst, the HPLC fingerprints of 44 batches of GSB from differentproducing areas were established, revealing 25 common peaks. Principal component analysis (PCA) and Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) of the 25 peak areas resulted in the identification of five components based on Variable Importance in Projection (VIP) values >1. Subsequently, these small-molecule components of GSB were screened for interaction with liver proteins, leading to the identification of three components with strong efficacy, namely, swertiamarin, gentiopicroside, and sweroside, which were designated as Q-markers of GSB associated with liver injury treatment. Furthermore, the therapeutic efficacy of these Q-markers was validated using a hydrogen peroxide-induced NCTC 1469 cell injury model. Finally, the Q-markers were quantified, and the quality of GSB samples from different origins was evaluated through PCA, entropy-weighted Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), and Hierarchical Cluster Analysis (HCA) based on the quantification results.DiscussionThe potential Q-markers of GSB were predicted through the integration of HPLC fingerprinting, pattern recognition, and small molecule–protein interaction analysis. Cell experiment results showed that swertiamarin, gentiopicroside, and sweroside significantly alleviated liver cell injury. Quantitative analysis of the Q-markers identified significant differences in their contents across GSB samples from different producing areas. This methodology provides a novel and comprehensive framework for defining Q-markers and evaluating GSB quality.